Experimental investigation of two‐stage humidification‐dehumidification desalination system integrated with an innovative oxy‐hydrogen (HHO) system. (25th January 2021) - Khairat Dawood, Mohamed M.; Amer, Ahmed; Teamah, Mohamed A.; Aref, Attia; Mansour, Tamer
Summary: The current research experimentally investigated a sustainable desalination method to maximize freshwater production at minimal costs. Solar photovoltaics are used as a source of clean and renewable energy. The system used in conducting the experiments consists of: an air heater, water heater, two stages of cross‐flow humidification, two stages of cross‐flow dehumidification, and an oxy‐hydrogen gas generator. The setup's working principle is the open‐air and closed water cycle. A centrifugal fan blows the ambient air to pass through the air heater. Air is heated through a heat exchanger, which is consequently heated by hot water. Water is heated using a new heating approach by using a mixture of 20% natural gas and 80% hydrogen gas with less impact on environmental pollution. Air is then humidified through two‐stage humidification systems using a high water temperature technique, then through the innovative vibrating plate circuit, respectively. The humidified air is condensed through two consecutive dehumidification heat exchangers. The system parameters are optimized to enhance freshwater productivity. The studied operative parameters are air mass flow rate, water mass ratio (WMR), and the effect of adding a second stage of humidification. The results showed that the maximum daily productivity is 49.3 kg/day. The optimum air mass flow rate and water mass ratio to obtain maximum productivity was found to be 0.375 kg/s and 0.6, respectively. Furthermore, the experiments' results showed that two‐stage humidification enhanced freshwater productivity by 23.25% than that of the single stage of humidification. Finally, an economical study analysis conducted for the test rig showed the cost per liter to be 0.0114 $/L, which is competitive when compared with previous work. Abstract : Schematic diagram of modified HDH Desalination System